Linking Green HRM Practices to Employees’ Pro-Environmental Behavior: The Mediating Role of Green Engagement - Radha, P; Lekshmy, S N; Sayyed, Nasreen; Priya, K (Journal of Nepal Commerce Association, 2025)
This study explores the impact of Green Human Resource Management (GHRM) practices on employees’ pro-environmental behavior (PEB) in the workplace, with a particular focus on the mediating role of green engagement. Grounded in the Ability–Motivation–Opportunity (AMO) framework, the study posits that green recruitment and selection, green training and development, and green performance management enhance employees’ environmental abilities and motivation, thereby fostering stronger engagement with organizational green initiatives. Increased green engagement is expected to encourage everyday pro-environmental behaviors, including energy conservation, waste reduction, and environmentally responsible work practices. A quantitative research design is proposed, using survey data collected from employees across organizations in a specified industry or country. Structural equation modeling (SEM) is suggested to examine both direct and indirect relationships among GHRM practices, green engagement, and PEB. The study is expected to contribute to HRM and sustainability literature by explaining the psychological mechanism linking GHRM to environmental behavior, while offering practical guidance for managers seeking to improve organizational environmental performance.